(untitled) (المجلة الدولية للبحوث العلمية, 2025)
Retinal diseases, including macular degeneration and diabetic retinopathy, are major causes of vision loss. Early and accurate diagnosis is essential for effective treatment and disease management. This study explores the role of mathematical models in diagnosing retinal diseases using Optical Coherence Tomography (OCT) and ultrasound imaging. By applying mathematical equations, such as refraction and reflection models in OCT and wave intensity models in ultrasound, we enhance the accuracy of detecting abnormalities in retinal tissues. Additionally, fluid dynamics equations, such as the Navier-Stokes equation, help analyze fluid movement within the eye. The integration of mathematical models with medical imaging improves diagnostic precision, aids in early detection, and contributes to better treatment planning. This study highlights the importance of mathematics in ophthalmology and demonstrates its potential in advancing retinal disease diagnosis.